INFLUENCE OF HUMAN EMOTIONS ON LEARNING. A LITERATURE REVIEW. - Santoyo Manzanilla, David de Jesús; Rivera de la Rosa, Alba Rosa; Ortiz Pech, Rafael (Perspectivas Docentes, 2025)
The purpose of this research is to analyze the influence of human emotions on the learning process in students at the primary and secondary levels, in order to guide possible strategies to consolidate solid and effective teaching for the benefit of the students. As part of the methodology, a documentary-type design was used through the systematic review of scientific research published in recognized scientific journals within the period 2017-2022, referring to the topic of human emotions and learning. To which both qualitative and quantitative analysis was applied to obtain the results. Likewise, this article in its results as the application of the PISA test (Programme for International Student Assessment) in 2018, demonstrated that learning levels have been deficient, since emotional education strategies are not taken into account within of the teaching processes, and it is concluded that the implementation of a solid emotional education can help guarantee complete and quality learning.